2020
DOI: 10.1186/s12879-020-05134-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with occurrence of salmonellosis among children living in Mukuru slum, an urban informal settlement in Kenya

Abstract: Background: In Kenya, typhoid fever and invasive non-typhoidal salmonellosis present a huge burden of disease, especially in poor-resource settings where clean water supply and sanitation conditions are inadequate. The epidemiology of both diseases is poorly understood in terms of severity and risk factors. The aim of the study was to determine the disease burden and spatial distribution of salmonellosis, as well as socioeconomic and environmental risk factors for these infections, in a large informal settleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
4
19
0
1
Order By: Relevance
“…Most of them (64%) suffered from acute illnesses such as fever, flu, diarrhoea and so on. It is noteworthy that the urban environment (particularly Dhaka, where the population density is so high and resources are scarce) may provide a favourable setting for the spread of various infectious diseases, especially in slums [ 35 , 36 , 42 ]. Further, migration and rapid urbanisation can result in new diseases from remote rural areas appearing in cities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them (64%) suffered from acute illnesses such as fever, flu, diarrhoea and so on. It is noteworthy that the urban environment (particularly Dhaka, where the population density is so high and resources are scarce) may provide a favourable setting for the spread of various infectious diseases, especially in slums [ 35 , 36 , 42 ]. Further, migration and rapid urbanisation can result in new diseases from remote rural areas appearing in cities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major explanatory variables utilised in this study are based on the socioeconomic factors of patients with acute and chronic diseases, following earlier studies in various urban settings [31,[34][35][36][37][38][39][40]. The age of the population is categorised into four groups (younger than 5, 5-14, 15-60 and older than 60).…”
Section: Major Explanatory Variablesmentioning
confidence: 99%
“…Our results and interpretation are consistent with and extend those of several previous reports. Firstly, in Kenya, iNTS infections caused by Salmonella Typhimurium or Enteritidis in an informal urban settlement were not found to be associated with the rearing of any domestic animals [48]. Secondly, in Burkina Faso the only isolates that matched the index cases were obtained from the stool of household members, despite extensive animal and water sampling in the households of iNTS patients [49].…”
Section: Discussionmentioning
confidence: 99%
“…This age group in Kenya comprises of young adults who are likely buy food from the streets with low standards of hygiene and therefore exposing them to foodborne diseases. A recent study reported that buying food from the street as a common behaviour for residents of Mukuru slums and found significant association of this habit with salmonella disease ( Mbae et al, 2020 ). This study found an inverse relationship between E. histolytica infections and diarrhea.…”
Section: Discussionmentioning
confidence: 99%